Pengaruh Celebrity Endorsement Dan Promosi Terhadap Keputusan Pembelian Produk Melalui Social Media Tiktok Shop - Aulia Nurjannah; Fitri Kumalasari; Ismanto Ismanto (Transformasi: Journal of Economics and Business Management, 2023)
. This research aims to determine: (1) The influence of celebrity endorsements on purchasing decisions (Study on TikTok Shop users in Kolaka Regency), (2) The influence of promotions on purchasing decisions (Study on TikTok Shop users in Kolaka Regency). This research uses a quantitative method approach. Data collection in this research used observation, documentation and questionnaires. The population of this research is TikTok Shop users in Kolaka Regency. Meanwhile, the sample for this research consisted of 130 respondents with sample determination using purposive sampling technique. Research instrument testing uses validity and reliability tests with SPSS 25.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with SmartPLS 4.0. Based on the research results, it is known that the Celebrity Endorsement variable has a positive and significant effect on Purchasing Decisions as indicated by a T-Statistic value of 2.871 and a P-Values ​​of 0.004. And the Promotion variable also has a positive and significant effect on Purchasing Decisions, this is shown by a T-Statistic value of 7.763 and a P-Values ​​of 0.000. Based on the research results, it is known that the Celebrity Endorsement variable has a positive and significant effect on Purchasing Decisions as indicated by a T-Statistic value of 2.871 and a P-Values ​​of 0.004. And the Promotion variable also has a positive and significant effect on Purchasing Decisions, this is shown by a T-Statistic value of 7.763 and a P-Values ​​of 0.000. Based on the research results, it is known that the Celebrity Endorsement variable has a positive and significant effect on Purchasing Decisions as indicated by a T-Statistic value of 2.871 and a P-Values ​​of 0.004. And the Promotion variable also has a positive and significant effect on Purchasing Decisions, this is shown by a T-Statistic value of 7.763 and a P-Values ​​of 0.000.